Genome-wide Association Study of Susceptibility Loci for Cervical Cancer - Chen, Dan; Juko-Pecirep, Ivana; Hammer, Joanna; Ivansson, Emma; Enroth, Stefan; Gustavsson, Inger; Feuk, Lars; Magnusson, Patrik K.E.; McKay, James D.; Wilander, Erik; Gyllensten, Ulf (JNCI : Journal of the National Cancer Institute, 2013)
Cervical carcinoma has a heritable genetic component, but the genetic basis of cervical cancer is still not well understood. We performed a genome-wide association study of 731 422 single nucleotide polymorphisms (SNPs) in 1075 cervical cancer case subjects and 4014 control subjects and replicated it in 1140 case subjects and 1058 control subjects. The association between top SNPs and cervical cancer was estimated by odds ratios (ORs) and 95% confidence intervals (CIs) with unconditional logistic regression. All statistical tests were two-sided. Three independent loci in the major histocompatibility complex (MHC) region at 6p21.3 were associated with cervical cancer: the first is adjacent to the MHC class I polypeptide-related sequence A gene (MICA) (rs2516448; OR = 1.42, 95% CI = 1.31 to 1.54; P = 1.6×10(-18)); the second is between HLA-DRB1 and HLA-DQA1 (rs9272143; OR = 0.67, 95% CI = 0.62 to 0.72; P = 9.3×10(-24)); and the third is at HLA-DPB2 (rs3117027; OR=1.25, 95% CI = 1.15 to 1.35; P = 4.9×10(-8)). We also confirmed previously reported associations of B*0702 and DRB1*1501-DQB1*0602 with susceptibility to and DRB1*1301-DQA1*0103-DQB1*0603 with protection against cervical cancer. The three new loci are statistically independent of these specific human leukocyte antigen alleles/haplotypes. MICA encodes a membrane-bound protein that acts as a ligand for NKG2D to activate antitumor effects. The risk allele of rs2516448 is in perfect linkage disequilibrium with a frameshift mutation (A5.1) of MICA, which results in a truncated protein. Functional analysis shows that women carrying this mutation have lower levels of membrane-bound MICA. Three novel loci in the MHC may affect susceptibility to cervical cancer in situ, including the MICA-A5.1 allele that may cause impaired immune activation and increased risk of tumor development.